Capacity building programme for student organisations: Fostering student engagement with the community: Program penguatan kapasitas organisasi kemahasiswaan: Membangun keterlibatan mahasiswa dengan masyarakat - Yonevi, Yusuf; Aprillia, Najwa Dinara; Haryani, Datik Wahyu; Admaja, Faiz Estu; Salsabilla, Niva (Sungging: Journal of Innovative, Cultural, Transdisciplinary Art and Kriya Discourse, 2025)
This study examines how fine arts students at Yogyakarta State University engaged with the community of Beji Village through a capacity-building programme. Using qualitative case studies and interviews with four participants, the findings show that students adapted art education to local socio-cultural contexts through informal communication, contextual media, and intergenerational collaboration. Beyond skill development, the experience enhanced cultural awareness and shifted students’ roles toward art facilitation. The initiative bridged academia and community while promoting local cultural identity through collaborative art. Recommendations include strengthening community-based curricula and sustained support to ensure lasting social impact. _______________________________________________________________________________   Penelitian ini mengkaji bagaimana mahasiswa seni rupa Universitas Negeri Yogyakarta berinteraksi dengan masyarakat melalui Program Penguatan Kapasitas Organisasi Kemahasiswaan (PPKO) di Desa Beji, Gunungkidul. Dengan pendekatan studi kasus, data dikumpulkan melalui wawancara semi-terstruktur terhadap empat mahasiswa. Hasil menunjukkan mahasiswa mampu menyesuaikan strategi pembelajaran seni dengan struktur sosial-budaya lokal melalui komunikasi informal, media kontekstual, dan pelibatan masyarakat lintas generasi dalam proses kreatif. Selain meningkatkan keterampilan teknis dan pedagogis, pengalaman ini memperluas kesadaran kultural mahasiswa serta mengubah peran mereka menjadi fasilitator seni. Proses ini menjembatani dunia akademik dengan realitas sosial sekaligus mengangkat identitas budaya lokal melalui praktik seni kolaboratif. Temuan merekomendasikan penguatan kurikulum berbasis komunitas dan pendampingan berkelanjutan untuk memastikan dampak sosial pendidikan seni yang berkelanjutan.